Hepatic Langerhans cell histiocytosis: Report of a rare case - Renling Yao; Jun Chen; Jie Li (Elsevier, 2023)
Langerhans cell histiocytosis (LCH) is a rare neoplastic disease characterized by abnormal proliferation of Langerhans cells infiltrating various organs, resulting in organ dysfunction. In some patients, the BRAFV600E mutation can be detected. Histopathology reveals a substantial proliferation of Langerhans cells, contributing significantly to the diagnosis of LCH. Clinical manifestations vary depending on the affected tissues or organs. LCH occurs less frequently in adults than in children, and clinicians often lack sufficient awareness of this disease, making it susceptible to misdiagnosis. In this report, a case of liver injury caused by Langerhans cell invasion is presented, as confirmed by a liver biopsy in adults.